2023
DOI: 10.2147/ijgm.s395281
|View full text |Cite
|
Sign up to set email alerts
|

Body Self-Perception, Dietary Self-Efficacy, and Body Mass Index in Young Adults: A Cross-Sectional Survey

Abstract: Background Body self-perception and dietary self-efficacy may represent an important factor in the prevention of excess body weight. Purpose This study evaluated body self-perception, dietary self-efficacy, and body mass index (BMI) in the Peruvian population. Methods A cross-sectional online survey was administered to 190 men and 210 women. Each participant was shown 9 Stunkard anatomical silhouettes corresponding to BMI values. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In addition to physical aspects, the perceptual dimension of body image is influenced by several factors that include emotional and socio-cultural aspects [ 14 ]. According to the complexity of this dimension, the adiposity measures explored in the present study (anthropometry or DXA) hardly explained the variability in the degree of distortion, especially among women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to physical aspects, the perceptual dimension of body image is influenced by several factors that include emotional and socio-cultural aspects [ 14 ]. According to the complexity of this dimension, the adiposity measures explored in the present study (anthropometry or DXA) hardly explained the variability in the degree of distortion, especially among women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that body image dissatisfaction caused by excess weight is frequently (from 59% to 82%) observed among women [ 11 , 14 16 ]. Previous studies have suggested that the pattern of female beauty frequently observed in Western cultures [ 33 , 34 ] is characterized by the search for thinness [ 14 , 34 ] which, at least in part, can explain this finding. Conversely, body dissatisfaction for men may be more diverse than for women: it included a concern with musculature and body shape [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation